Special contoured pelvic brim reconstruction titanium plate combined with trans-plate buttress screws (quadrilateral screws) for acetabular fractures with quadrilateral plate involvement through the anterior ilioinguinal approach - Wang, Wei; Cai, Xianhua; Liu, Ximing; Wang, Guodong; Kang, Hui; Qian, Shenglong (Frontiers in Surgery, 2024)
BackgroundManaging complicated acetabular fractures involving the quadrilateral plate (QLP) can be challenging for surgeons, especially when complicated by comminution and osteoporosis. Traditional implants do not provide sufficient fixed strength or a proper match. The new-type pre-contoured infrapectineal buttress plates may have drawbacks, such as inaccurate fitting on the medial surface of QLP and an inability to apply reversed compression force to resist medial displacement of femoral head. Therefore, the primary purpose of this study is to introduce a novel technique that utilizes a special contoured pelvic brim reconstruction titanium plate combined with quadrilateral screws to reduce and stabilize acetabular fractures involving the QLP through the ilioinguinal approach. Additionally, the secondary purpose is to evaluate both clinical effectiveness and radiological outcomes of this technique for QLP fractures.MethodsWe conducted a retrospective analysis of prospectively collected data from 48 patients (31 males and 17 females) who suffered from acute displaced fractures of the QLP and were treated between January 2012 and December 2019 using a special contoured plate combined with quadrilateral screws. The patients' mean age was 47.56 ± 11.31 years (range: 19–73 years). Fracture patterns included 20 both-column fractures, 12 anterior column and posterior hemitransverse fractures, eight T-type fractures, five transverse fractures and three anterior column fractures with the QLP affected, all of which had femoral head protrusion. Immediate postoperative reduction quality was evaluated according to Matta's criteria. Final clinical functions were assessed during follow-up using the modified Merle d’Aubigné and Harris Hip scores (HHS).ResultsThe patients were followed up for an average of 48.36 ± 12.94 months (ranging from 24 to 84 months). The mean operative time was 246.08 ± 54.30 min (ranging from 178 to 397 min), and the average blood loss was 715.16 ± 263.84 ml (ranging from 400 to 2000ml). The radiological grading at postoperative stage showed anatomical reduction in 30 patients (62.50%), satisfactory reduction in 14 patients (29.17%), and poor reduction in four patients (8.33%). At the final follow-up, no re-protrusion of the femoral head was observed. In terms of functional outcome, the mean modified Merle d’Aubigné-Postel score was excellent in 26 patients (54.17%), good in 17 patients (35.42%), fair in four patients (8.33%), and poor in one patient (2.08%). The HHS was excellent in 23 patients (47.92%), good in 20 patients (41.67%), fair in four patients (8.33%), and poor in one patient (2.08%). The average HHS was 87.38 ± 7.86 (ranging from 52 to 98). Postoperative complications included lateral femoral cutaneous nerve injury in two patients, delayed wound healing and subsequent development of an inguinal hernia in one patient. Late complications were observed in two patients, with one case of heterotopic ossification and another case of post-traumatic osteoarthritis underwent hip arthroplasty within two years after surgery.ConclusionOur results indicate that employing the contoured plate specifically designed for QLP injuries, in conjunction with quadrilateral screws through the ilioinguinal approach, can lead to positive outcomes in the treatment of displaced acetabular fractures involving the QLP. This straightforward and efficient technique offers a viable option for surgeons who are managing complex acetabular fractures.